Pelatihan dan Pendampingan Penyusunan Laporan Keuangan Sederhana Pada UMKM di Kelurahan Kalitirto dan Kelurahan Sukoharjo - Elvinda Trias Putri; Hasim As’ari (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The success and survival of MSMEs is highly dependent on their ability or capacity to manage finances effectively. However, many MSMEs experience obstacles as well as challenges so that they have difficulty in compiling correct and accurate financial statements due to limited access to resources and knowledge. This program aims to improve the ability of MSMEs in Kalitirto and Sukoharjo Villages to make simple financial statements. Through this program, it is hoped that MSMEs can understand the importance of financial statements and be able to calculate their business profits and losses. The method used is socialization to provide an understanding of the importance of financial statements for MSMEs, followed by training and assistance in the process of making them. This program can significantly contribute to improving the competence of MSMEs in the field of accounting, especially in terms of preparing financial statements.